Cation Substitution Induced d‐Band Center Modulation on Cobalt‐Based Spinel Oxides for Catalytic Ozonation - Qu, Wei; Tang, Zhuoyun; Tang, Su; Wen, Hailin; Fang, Jingyun; Lian, Qiyu; Shu, Dong; He, Chun (Advanced functional materials, 2023)
Co 3 O 4 spinel is a promising transition metal oxide (TMO) catalyst for the catalytic ozonation of volatile organic compounds (VOCs). Herein, metal–organic frameworks (MOFs)‐derived Ni‐ and Mg‐ substituted Co 3 O 4 catalysts retain similar spinel structures, but display improved and reduced ozonation performance of methyl mercaptan (CH 3 SH), respectively. Remarkably, the NiCo 2 O 4 catalyst can still ≈90% removal of CH 3 SH after running for 20 h at room temperature under an initial concentration of 50 ppm CH 3 SH and 40 ppm O 3 , relative humidity of 60%, and space velocity of 300 000 mL h −1 g −1 , exceeding the reported values. Experimental characterizations have unveiled that the substitution of Ni and Mg into the Co 3 O 4 spinel altered surface acidity, oxygen species mobility, and Co 2+ /Co 3+ ratio. The in situ Raman spectra reveal the dynamic formation Co(III)‐O ad * via the transformation of O 3 into surface atomic oxygen (O ad *) and peroxide species (O 2 *). Theoretical calculations verify that Ni‐substitution increases nonuniform charges and Fermi density, leading to a moderate increase in d‐band center energy levels, thereby promoting O 3 specific adsorption/activation to convert O ad */O 2 * and •OH/ 1 O 2 /•O 2 − , which contributes to eliminate CH 3 SH and prevent poisoning. The concept of tuning the d‐band center can provide valuable insights for the design of other catalysts for catalytic ozonation.